O uso de TDICs na rede municipal de porto alegre: uma análise da práxis do professor articulador de inovação - Rosa, Aline Brandalize Schwartzhaupt da (Universidade do Vale do Rio dos Sinos, 2024)
In the 21st century, society faces political, economic, and social changes, characterized by a new rationality that is being established. Human relationships are increasingly mediated by digital technologies, which directly impacts education. In this context, this research aimed to analyze the practice developed by the Innovation Coordinator Teacher to promote the use of Digital Technologies of Information and Communication (DTICs) in schools within the Porto Alegre Municipal Education Network (RME) and how it responds to the pedagogical needs of the Network. The research addressed school managers, teachers, students from Elementary Education, and children from Early Childhood Education within the RME/Poa, with the primary focus being on the Innovation Coordinator Teachers. The methodological bases of the investigation included bibliographic and documentary review, as well as questionnaires and interviews, which were systematized and analyzed through Content Analysis. Digital forms and voice recordings were used to collect data. The action research that guided the study resulted in a formative proposal aimed at the practice of the Innovation Coordinator Teachers. Regarding the role of the coordinator teacher in using DTICs, it was observed that school managers recognize the importance of the coordinator teacher as an agent for implementing DTICs, considering them essential for promoting innovation in educational practices. However, they emphasize the need for institutional support and continuous training to strengthen teaching practices. Teachers value the coordinator's role as a facilitator and motivator of learning, but they face resistance from some colleagues and a lack of time for training and planning. Students, in turn, appreciate more dynamic and interactive lessons, which are often provided through the use of technologies. They expect teachers to be proficient in DTICs and create relevant and engaging learning experiences. In general terms, perceptions vary among the groups, and the data suggest that creating a collaborative and supportive environment can enhance the effectiveness of the coordinator teacher and facilitate the integration of DTICs into the teaching and learning process.
Keywords: Práxis pedagógica; TDICs; Currículo; Cidadania digital; Gestão da Educação Básica; Pedagogical praxis; ICTs; Curriculum; Digital citizenship; Basic Education Management; ACCNPQ::Ciências Humanas::Educação